Canthal V-plasty for Floppy Eyelid Surgery. Issue 10 (October 2019) - Phillips, Margaret E.; Fowler, Brian T.; Dryden, Stephen C.; Fleming, James C.
Abstract : Summary: The purpose of this article is to present a modified approach to the reconstruction of the upper and lower eyelids in floppy eyelid syndrome. A retrospective chart review was performed on all floppy eyelid patients who underwent simultaneous tightening of the upper and lower eyelid with a lateral tarsal strip, using a V-shaped incision in the lateral canthus, at University of Tennessee Hamilton Eye Institute from 2011 to 2012. Preoperative symptoms, surgical outcomes, complication rates, and postoperative symptoms were recorded. Nine eyes of 7 patients who underwent surgical correction for symptomatic floppy eyelids were included. All patients noted improvement in symptoms postoperatively, after reduction in the laxity of the upper and lower eyelid. Postoperative complications included buried lashes in the lateral canthus in 1 eye and a pyogenic granuloma in the lateral canthus of 1 eye. An excellent cosmetic outcome was noted in 78% (7/9) of eyes. No patients reported dissatisfaction nor required secondary surgical correction. The lateral canthal "V" incision provides an additional approach in the successful management of floppy eyelid syndrome involving the upper and lower eyelids. The design of the incision allows for excellent exposure of the lateral canthus for shortening of the eyelids with tarsal strip fixation, and it preserves the lateral canthal skin and canthus architecture. Further, the "V" incision is easily continued into the eyelid crease for blepharoplasty and ptosis repair when necessary. Abstract : Supplemental Digital Content is available in the text.